2018
DOI: 10.1002/eat.22833
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' perspective on an app for patient self‐monitoring in eating disorder treatment

Abstract: Recovery Record induced new and affected pre-existing treatment and work conditions for clinicians. Clinicians were preoccupied with challenges associated with the app, for example, an added work load and potential harm to the patient-clinician collaboration. Thus, prior to adopting the app, we encourage clinicians and managements to discuss the objectives, advantages and disadvantages of adopting the app, and outline specific guidelines for patient and clinician app usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Furthermore, the patients’ perception of treatment workload may depend on their abilities to counteract the ED pathology in general; in ED treatment, a common challenge is the egosyntonic nature of some ED symptoms and patients’ ambivalence toward some treatment activities, for example, weight gain [ 48 ]. Finally, the clinicians’ reception of the training on how to use RR and with that their specific RR usage [ 49 ] may also influence the patients’ experiences of treatment workload. Thus, minimally disruptive medicine might be especially complicated to apply in ED treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the patients’ perception of treatment workload may depend on their abilities to counteract the ED pathology in general; in ED treatment, a common challenge is the egosyntonic nature of some ED symptoms and patients’ ambivalence toward some treatment activities, for example, weight gain [ 48 ]. Finally, the clinicians’ reception of the training on how to use RR and with that their specific RR usage [ 49 ] may also influence the patients’ experiences of treatment workload. Thus, minimally disruptive medicine might be especially complicated to apply in ED treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice is in need of explicit guidelines on the usage of apps in ED treatment [ 49 ]. Although the specific content and design of such guidelines require more research, our study outlines possible recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Experts of technology‐based mental health tools emphasize the importance of adopting a user‐centric approach, lest the tools remain unused (Taylor et al, 2019). Featured next are three articles providing data about patients' (Linardon, Shatte, Tepper, & Fuller‐Tyszkiewicz, 2020; Neumayr, Voderholzer, Tregarthen, & Schlegl, 2019) perspectives on and examining clinicians' (Lindgreen, Clausen, & Lomborg, 2018) experiences with technology tools used in the treatment of eating disorders.…”
Section: Patients' and Therapists' Perspectives On Technology Toolsmentioning
confidence: 99%
“…Various applications have been developed to help patients accomplish self‐monitoring via mobile phone or online entry (Bauer & Moessner, 2013). In their paper entitled “Clinicians' perspective on an app for patient self‐monitoring in eating disorder treatment,” Lindreen and colleagues describe a qualitative study of clinicians' experience with integrating Recovery Record into their practice with eating disorder patients (Lindgreen et al, 2018). The clinicians recognized the value in being able to monitor patients' self‐monitoring records.…”
Section: Patients' and Therapists' Perspectives On Technology Toolsmentioning
confidence: 99%
“…They found clinically significant improvements (defined as at least a 0.5 SD reduction in global EDE‐Q score) in 40% of users (Darcy et al, n.d.). Furthermore, there are two qualitative evaluations of RR in a clinical sample, one from the patients' and one from the clinicians' perspective (Lindgreen, Clausen, & Lomborg, ; Lindgreen, Lomborg, & Clausen, ). The studies found that the acceptance of the app mainly depends on individual factors of the user.…”
Section: Introductionmentioning
confidence: 99%